WHITE CURCUMA EXTRACT (CURCUMA ZEDOARIA [CHRISTM.] ROSCOE) AMELIORATES INSULIN RESISTANCE BY MODULATING LIPID METABOLISM IN HIGH-FAT DIET-INDUCED WISTAR RATS - NOVI IRWAN FAUZI; KUSNANDAR ANGGADIREDJA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aims to examine the mechanism by which white turmeric extract inhibits insulin resistance in experimental animals. Methods: Twenty-five male Wistar rats were divided into five groups: Normal control, high-fat diet (HFD), drug control (metformin), and two dose groups of white turmeric extract (200 mg/kg and 400 mg/kg). A HFD was administered for 10 days to induce insulin resistance, except in the normal control group. The drug control and two extract groups received metformin (45 mg/kg), and white turmeric extract (200 mg/kg and 400 mg/kg) for an additional 10 days. Insulin resistance was assessed using fasting blood glucose, insulin levels, homeostasis model assessment of insulin resistance (HOMA-IR) index, fat profiles, and tissue morphology of liver and brain organs. Results: Rats given 400 mg/kg of white turmeric extract showed significantly lower fasting blood glucose (45.04±9.08 mg/dL), insulin levels (1.58±0.37 mU/L), and HOMA-IR index (0.17±0.02) compared to the HFD group (81.55±13.94 mg/dL, 2.28±0.20 mU/L, and 0.46±0.08, respectively). The extract improved fat profiles and caused morphological changes in liver and brain tissue, with liver cells appearing smaller and nerve cells showing longer axons. Conclusion: White turmeric extract effectively inhibits insulin resistance by improving fat profiles.